Hunangofiant Huw Erith - Llanw Braich, Trai Bylan - Erith, Huw (Y Lolfa, 2014)
The autobiography of a fisherman and countryman from the Llŷn peninsula, including a portrayal of his locality, family and the twists and turns of his life, with some stories about colourful colourful characters from Pen Llŷn. 29 colour and 7 black-and-white photographs.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books